Farmer seed networks make a limited contribution to agriculture? Four common misconceptions. (October 2015) - Coomes, Oliver T.; McGuire, Shawn J.; Garine, Eric; Caillon, Sophie; McKey, Doyle; Demeulenaere, Elise; Jarvis, Devra; Aistara, Guntra; Barnaud, Adeline; Clouvel, Pascal; Emperaire, Laure; Louafi, Sélim; et al.
Highlights: Food and agricultural policy undervalues farmer seed networks. These networks are important globally in circulating planting material among farmers. We challenge four common misconceptions in policy and practice about seed networks. Farmer seed networks are efficient and open but also selective in seed provisioning. Commercialization and regulation are unlikely to eradicate farmer seed networks. Abstract: The importance of seed provisioning in food security and nutrition, agricultural development and rural livelihoods, and agrobiodiversity and germplasm conservation is well accepted by policy makers, practitioners and researchers. The role of farmer seed networks is less well understood and yet is central to debates on current issues ranging from seed sovereignty and rights for farmers to GMOs and the conservation of crop germplasm. In this paper we identify four common misconceptions regarding the nature and importance of farmer seed networks today. (1) Farmer seed networks are inefficient for seed dissemination. (2) Farmer seed networks are closed, conservative systems. (3) Farmer seed networks provide ready, egalitarian access to seed. (4) Farmer seed networks are destined to weaken and disappear. We challenge these misconceptions by drawing upon recent research findings and the authors' collective field experience in studying farmer seed systems in Africa, Europe, Latin America and Oceania. Priorities for future research are suggested that would advance our understanding of seed networks and better inform agricultural and food policy.